Implementation of Character Values of Environmental Care in Geography Learning at SMA Negeri 1 Kinali - Jambak, Arnapis (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research aims to discuss and analyze how teachers and school leadership roles in implementing character values of environmental care in teaching geography to learners in SMA Negeri 1 Kinali. This study used a qualitative approach that aimed to describe the systematic, factual, and accurate information on the phenomenon in detail. Selection of the subject of research was conducted by the method of purposive sampling, where the School leaders, teachers, and learners with data collection through observation, interviews, and documentation based on the validity of the data with triangulation techniques and perseverance observation. In analyzing the data, the researcher used stages: data reduction, data presentation, and inference. The results of the study are as follows: 1) The school environment plays an important role in shaping the behavior of learners, 2) How teachers implement the character values in shaping the attitude of the environment care which was done by: (a) Integrating into the planning and implementation of learning geography through the preparation of syllabus, RPP and material by incorporating the values of characters in accordance with the demands of SK and KD, (b) organizing a routine activity held by the school, 3) the role of school leaders in the formation of the character values of learners with: (a) Development of school curriculum through the regulatory policies of the school and extra-curricular activities so as to establish the values of the expected character. (b) Development exemplary school leaders and teachers in motivating learners and cultural activities of the school, 4) How learners implement the values of character care about the environment through self-development program in schools and school activities related to the character values of environmental care, 5) Barriers to implement the characters values in SMA 1 Kinali due to school rules are not optimally running, so that the students' participation is still low in preserving the environment, lack of awareness of students to care about the environment both at school and at home, and yet optimal work together with the parents of students in the formation of character values for caring environment on the learner.